Quantification of southwest China rainfall during the 8.2 ka BP event with response to North Atlantic cooling - Y. Liu; C. Hu (Climate of the Past, 2016)
The 8.2 ka BP event could provide important information for predicting abrupt climate change in the future. Although published records show that the East Asian monsoon area responded to the 8.2 ka BP event, there is no high-resolution quantitative reconstructed climate record in this area. In this study, a reconstructed 10-year moving average annual rainfall record in southwest China during the 8.2 ka BP event is presented by comparing two high-resolution stalagmite δ 18 O records from Dongge cave and Heshang cave. This decade-scale rainfall reconstruction is based on a central-scale model and is confirmed by inter-annual monitoring records, which show a significant positive correlation between the regional mean annual rainfall and the drip water annual average δ 18 O difference from two caves along the same monsoon moisture transport pathway from May 2011 to April 2014. Similar trends between the reconstructed rainfall and the stalagmite Mg ∕ Ca record, another proxy of rainfall, during the 8.2 ka BP period further increase the confidence of the quantification of the rainfall record. The reconstructed record shows that the mean annual rainfall in southwest China during the central 8.2 ka BP event is less than that of present (1950–1990) by ∼ 200 mm and decreased by ∼ 350 mm in ∼ 70 years experiencing an extreme drying period lasting for ∼ 50 years. Comparison of the reconstructed rainfall record in southwest China with Greenland ice core δ 18 O and δ 15 N records suggests that the reduced rainfall in southwest China during the 8.2 ka BP period was coupled with Greenland cooling with a possible response rate of 110 ± 30 mm °C −1 .